Oxford international primary English student book 2 - Yeomans, Anna; Snashall, Sarah (Karachi ; Oxford university press, 2021)
Oxford international primary English book 2 (Second edition) serves up a delicious feast of words and fun! This vibrant textbook takes children on a captivating journey through the second level of language mastery, building upon the foundations laid in Book 1. Expanding their confidence and skills in reading, writing, speaking, and listening.
Keywords: English - Text book; Oxford - English text book